Porcelainized flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material capable of being sintered and foamed at low temperature as well as preparation method and application of porcelainized flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material
Preparation of ceramic-enhancing flame-retardant PDMS/hydroxyapatite nanofiber silicone rubber composite material by liquid phase blending method, solving the problem that it is difficult to form lightweight and porous ceramic structures at high temperatures in the prior art, and realizing the low temperature conditions Foaming expansion improves flame retardant and thermal insulation performance, suitable for construction and electronics and electrical fields.
Patent Information
- Application Number
- CN202411535713.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
AI Technical Summary
The existing porcelain-encapsulated silicone rubber composites are difficult to form lightweight and porous ceramic structures under high temperature or flame, which limits the improvement of their flame retardant and thermal insulation properties. The sintering process is complicated and it is difficult to achieve low-temperature foam expansion.
The liquid phase blending method is used to blend end vinyl polydimethylsiloxane, hydroxyapatite nanofibers, aluminum hydroxide, zinc borate and low-melting glass powder through liquid phase blending, vacuum defoaming and hot pressing molding. Prepare ceramic-resistant PDMS/hydroxyapatite nanofiber silicone rubber composite material to form a lightweight and porous ceramic body.
It realizes foam expansion under low temperature conditions, forming a lightweight, porous ceramic body with excellent flame retardant and heat insulation properties, significantly improving the comprehensive performance of the material, and is suitable for the construction and electronic and electrical fields.
Smart Images

Figure CN119264674A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flame-retardant silicone rubber materials, and relates to a flame-retardant PDMS silicone rubber composite material that can be ceramicized under high temperature or flame, and specifically relates to a ceramicizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material that can be sintered and foamed at low temperature, a preparation method and an application thereof. Background Art
[0002] The ceramic flame-retardant silicone rubber composite material has the excellent toughness and strength of silicone rubber under normal conditions. When it is attacked by high temperature or flame, it will be transformed into a ceramic body with high temperature resistance, ablation resistance, flame retardancy, and heat insulation. It can effectively prevent the spread of flames and heat diffusion. It has now become a hot spot in the fields of construction, aerospace, automobiles, electronics, etc. as a thermal protection material. Its excellent flexibility under normal conditions makes up for the deficiency that traditional ceramic materials cannot be used as soft materials. However, most of the existing research on ceramic silicone rubber composite materials tends to densify the ceramic body. In addition to the inherent properties of ordinary ceramics, porous ceramic materials also have the advantages of low density, high specific surface area and low thermal conductivity due to their unique pore structure. Due to its outstanding thermal insulation and high temperature resistance, it is widely used in various fields such as construction and military industry as a new type of fireproof and thermal insulation material.
[0003] Hydroxyapatite nanofibers are stable and easy to synthesize. Their high thermal stability also makes them useful as refractory fillers to improve the flame retardant properties of materials. Chinese invention patent CN 108238595A provides a composite aerogel made of hydroxyapatite nanofibers and microcrystalline cellulose. The aerogel has excellent flame retardant and smoke suppression effects, significantly improving the fire safety of the aerogel.
[0004] The present invention attempts to prepare a porcelainizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material by adding hydroxyapatite nanofiber as a porcelain filler, aluminum hydroxide as a flame retardant, zinc borate and a low-melting-point glass powder as a flux, and hydrogen-containing silicone oil as a curing agent to vinyl-terminated polydimethylsiloxane, and adopts liquid phase blending, vacuum degassing and hot pressing molding processes. The composite material can foam and expand during the sintering process to form a lightweight, porous ceramic structure that can effectively prevent the spread of flame and heat diffusion, thereby improving the comprehensive properties of the material such as flame retardancy, porcelain formation and heat insulation. Summary of the invention
[0005] The purpose of the present invention is to provide a low-temperature sintered and foamed porcelain-like flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material, a preparation method and an application thereof. The composite material has excellent flame retardant properties and can foam and expand during pyrolysis and combustion to form a lightweight, porous ceramic body with flame retardant and heat-insulating effects. The composite material has broad application prospects in the fields of construction, wires and cables, etc.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A low-temperature sintering and foaming porcelainizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material is made of the following raw materials in parts by weight:
[0008] 85-93 parts of vinyl-terminated polydimethylsiloxane as liquid silicone rubber base;
[0009] 7 to 15 parts of hydrogenated silicone oil as a curing agent;
[0010] 11 to 15 parts of hydroxyapatite nanofibers as a ceramic filler;
[0011] 25-35 parts of aluminum hydroxide as a flame retardant;
[0012] 40-55 parts of zinc borate and 7-10 parts of low melting point glass powder are used as flux.
[0013] As a preferred technical solution of the present invention, in the porcelainizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material that can be sintered and foamed at low temperature, the weight ratio between the PDMS component composed of terminal vinyl polydimethylsiloxane and hydrogen-containing silicone oil and the filler component composed of hydroxyapatite nanofibers, aluminum hydroxide, zinc borate, and low-melting point glass powder is 100:85-115.
[0014] The present invention also proposes a method for preparing the above-mentioned composite material, firstly synthesizing hydroxyapatite nanofibers by a hydrothermal method, then adding hydroxyapatite nanofibers, zinc borate, aluminum hydroxide and low-melting-point glass powder into vinyl-terminated polydimethylsiloxane, stirring and mixing evenly, then adding hydrogen-containing silicone oil and continuing to stir evenly to obtain a pre-made slurry; transferring the pre-made slurry into a mold, placing it in a vacuum oven for vacuum degassing at room temperature, and finally hot pressing and cooling and demolding to obtain a porcelain-like flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material that can be sintered and foamed at a low temperature.
[0015] As a preferred technical solution of the present invention, the preparation steps of synthesizing hydroxyapatite nanofibers by hydrothermal method are as follows: cetyltrimethylammonium chloride and oleic acid are added to an ethanol / deionized water solution and magnetically stirred at room temperature for a period of time, and then calcium chloride solution, sodium hydroxide solution and sodium dihydrogen phosphate solution are slowly added in sequence and stirred for a period of time to prepare a precursor solution, and then the precursor solution is transferred to a hydrothermal reactor for hydrothermal reaction; after the reaction is completed, the precipitate is washed with ethanol and deionized water, and finally dried to obtain hydroxyapatite nanofibers.
[0016] Further preferably, in the method for synthesizing hydroxyapatite nanofibers, the stirring time during the preparation of the precursor solution is 20 to 30 minutes, and the molar ratio of Ca / P in the prepared precursor solution is 1.14: 1. The hydrothermal reaction temperature is 160 to 200° C., and the hydrothermal reaction time is 20 to 30 hours. The drying temperature is 60 to 80° C., and the drying time is 8 to 12 hours.
[0017] As a preferred technical solution of the present invention, in the preparation method of the composite material, the stirring rate during the preparation of the pre-slurry is 200-400 rpm, the total stirring time is 5-10 min, the vacuum degassing time is 60-120 min, the hot pressing molding temperature is 100-150° C., and the hot pressing molding time is 5-10 min.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0019] The ceramic flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material that can be sintered and foamed at low temperature proposed by the present invention is prepared by liquid phase blending, vacuum degassing treatment and hot pressing molding process of terminal vinyl polydimethylsiloxane, hydrogen-containing silicone oil, hydroxyapatite nanofiber, zinc borate, aluminum hydroxide and low-melting point glass powder. The solution blending method used is simple in process and easy to process, which helps to evenly disperse the components in the PDMS system. The use of hydroxyapatite nanofiber as a ceramic filler helps to optimize the ceramic performance and flame retardant performance of the PDMS silicone rubber composite material. At the same time, the ceramic flame-retardant PDMS silicone rubber composite material prepared by the present invention can effectively improve the limiting oxygen index, and can foam and expand during the sintering process to form a lightweight, porous ceramic body, showing good heat insulation and material insulation effects, and has broad application prospects in the fields of wires and cables, electronic appliances, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope image of the hydroxyapatite nanofibers prepared in Example 2.
[0021] Figure 2 The limiting oxygen index and vertical burning test rating of the porcelainizable flame-retardant PDMS silicone rubber composite materials prepared in Example 1, Example 2, Example 3 and Example 4 are shown.
[0022] Figure 3 This is a scanning electron microscope image of the porcelainizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material prepared in Example 4 after sintering at 850° C. in a muffle furnace. DETAILED DESCRIPTION
[0023] The following is a further detailed description of a low-temperature sinterable and foamable porcelain-like flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material, a preparation method and an application of the present invention in conjunction with the embodiments and the accompanying drawings.
[0024] First, as a specific embodiment of the present invention, the raw material models and manufacturers used to prepare hydroxyapatite nanofibers and porcelainizable flame-retardant PDMS silicone rubber composite materials are:
[0025] Hexadecyltrimethylammonium chloride was purchased from Shanghai Zhanyun Chemical Co., Ltd., model C 19 H 42 ClN.
[0026] Oleic acid was purchased from Sinopharm Chemical Reagent Co., Ltd., model C 18 H 34 O2.
[0027] Anhydrous calcium chloride was purchased from Xilong Scientific Co., Ltd., model number CaCl2.
[0028] Sodium hydroxide was purchased from Sinopharm Chemical Reagent Co., Ltd., model: NaOH.
[0029] Sodium dihydrogen phosphate was purchased from Xilong Scientific Co., Ltd. with the model number of NaH2PO4·2H2O.
[0030] Vinyl-terminated polydimethylsiloxane was purchased from Jinpin Instrument Equipment Co., Ltd., model number SYLGARD 184.
[0031] Hydrogenated silicone oil was purchased from Jinpin Instrument Equipment Co., Ltd., model SYLGARD 184.
[0032] Aluminum hydroxide was purchased from Shenzhen Haiyang Powder Technology Co., Ltd., model ATH-1.
[0033] Zinc borate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with the model number of 2ZnO·3B2O3·3.5H2O.
[0034] Low melting point glass powder was purchased from Shenzhen Haiyang Powder Technology Co., Ltd., model LG45.
[0035] Example 1
[0036] Preparation of a pure PDMS silicone rubber composite blank sample includes the following steps:
[0037] Weigh 90.9 g of vinyl-terminated polydimethylsiloxane, add 9.1 g of hydrogenated silicone oil, and stir at 300 rpm for 5 min to obtain a pre-made slurry; transfer the pre-made slurry into a mold, place it in a vacuum oven and vacuum degas for 120 min at room temperature; after degassing, place the mold in a flat-plate hot pressing molding machine and hot press at 150°C for 5 min, and obtain a pure PDMS silicone rubber composite material after cooling and demolding.
[0038] Example 2
[0039] Preparation of a porcelainizable flame-retardant PDMS silicone rubber composite material using hydroxyapatite nanofibers as a porcelain-forming filler comprises the following steps:
[0040] 1. Add 1.33g hexadecyltrimethylammonium chloride and 50mL oleic acid to 80mL ethanol / deionized water solution (ethanol: deionized water = 5:3) and stir magnetically at room temperature for a period of time, then slowly add 50mL calcium chloride solution (30mg / mL), 50mL sodium hydroxide solution (70mg / mL) and 66mL sodium dihydrogen phosphate solution (28mg / mL) in sequence and stir for 30min respectively to prepare the precursor solution, and then transfer the precursor solution to the hydrothermal reactor for hydrothermal reaction at a reaction temperature of 180℃ and a hydrothermal reaction time of 24h. After the reaction, wash the precipitate with ethanol and deionized water, and finally dry it to obtain hydroxyapatite nanofibers at a drying temperature of 80℃ and a drying time of 8h.
[0041] Figure 1 This is a scanning electron microscope image of the hydroxyapatite nanofibers prepared in Example 2. It can be seen that the hydroxyapatite nanofibers are self-assembled into bundles.
[0042] 2. Weigh 90.9g of vinyl-terminated polydimethylsiloxane, add 11.09g of hydroxyapatite nanofibers, 40.65g of zinc borate, 25.87g of aluminum hydroxide and 7.39g of low-melting glass powder in sequence, stir mechanically at 200rpm for 5min, add 9.1g of hydrogenated silicone oil, continue stirring at 200rpm for 5min to obtain a pre-made pulp; transfer the pre-made pulp into a mold, place it in a vacuum oven and vacuum degas for 120min at room temperature; after degassing, place the mold in a flat vulcanizer and hot press at 150℃ for 5min, and obtain a porcelainizable flame-retardant PDMS silicone rubber composite material after cooling and demolding. Among them, the mass ratio of PDMS component to all filler components (hydroxyapatite nanofibers + zinc borate + aluminum hydroxide + low-melting glass powder) is 100:85.
[0043] Example 3
[0044] Preparation of a porcelainizable flame-retardant PDMS silicone rubber composite material using hydroxyapatite nanofibers as a porcelain-forming filler comprises the following steps:
[0045] Weigh 90.9g of vinyl-terminated polydimethylsiloxane, add 13.04g of hydroxyapatite nanofibers (prepared in Example 2), 47.83g of zinc borate, 30.43g of aluminum hydroxide and 8.7g of low-melting glass powder in sequence, stir mechanically at 300rpm for 5min, add 9.1g of hydrogenated silicone oil, continue stirring at 300rpm for 5min to obtain a pre-slurry; transfer the pre-slurry into a mold, place it in a vacuum oven for vacuum degassing at room temperature for 120min; after degassing, place the mold in a flat vulcanizer and hot press at 100℃ for 5min, and obtain a porcelainizable flame-retardant PDMS silicone rubber composite material after cooling and demolding. Among them, the mass ratio of PDMS component to all filler components (hydroxyapatite nanofibers + zinc borate + aluminum hydroxide + low-melting glass powder) is 100:100.
[0046] Example 4
[0047] Preparation of a porcelainizable flame-retardant PDMS silicone rubber composite material using hydroxyapatite nanofibers as a porcelain-forming filler comprises the following steps:
[0048] Weigh 90.9g of vinyl-terminated polydimethylsiloxane, add 15g of hydroxyapatite nanofiber (prepared in Example 2), 55g of zinc borate, 35g of aluminum hydroxide and 10g of low-melting glass powder in sequence, stir mechanically at 400rpm for 5min, add 9.1g of hydrogenated silicone oil, continue stirring at 400rpm for 5min to obtain a pre-slurry; transfer the pre-slurry into a mold, place it in a vacuum oven for vacuum degassing at room temperature for 120min; after degassing, place the mold in a flat vulcanizer and hot press at 100℃ for 5min, and obtain a porcelainizable flame-retardant PDMS silicone rubber composite material after cooling and demolding. Among them, the mass ratio of PDMS component to all filler components (hydroxyapatite nanofiber + zinc borate + aluminum hydroxide + low-melting glass powder) is 100:115.
[0049] Figure 2 The limiting oxygen index and vertical burning test rating of the pure PDMS silicone rubber in Example 1 and the porcelainizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composites prepared in Examples 2, 3 and 4 are shown. Figure 2 As shown, the vertical burning test ratings of the porcelainizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composites prepared in Examples 2, 3 and 4 are V-1, V-1 and V-0, respectively. At the same time, the limiting oxygen index of Example 4 is 41.5, which is 76.6% higher than 23.5 of the pure PDMS silicone rubber in Example 1.
[0050] Figure 3 This is a scanning electron microscope picture of the ceramicizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material prepared in Example 4 with hydroxyapatite nanofiber as ceramic filler after sintering at 850°C in a muffle furnace. Figure 3 As shown in Figure 2, the composite material foamed and expanded during the sintering process, forming an internal porous and ordered closed-cell ceramic structure with a sintered density of 0.471±0.031g / cm 3 This lightweight and porous structure is conducive to improving flame retardant and heat insulation properties.
[0051] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A low-temperature sinterable and foamable ceramic flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material, characterized in that: Made from the following raw materials in parts by weight: 85-93 parts of vinyl-terminated polydimethylsiloxane as liquid silicone rubber base; 7 to 15 parts of hydrogenated silicone oil as a curing agent; 11 to 15 parts of hydroxyapatite nanofibers as a ceramic filler; 25-35 parts of aluminum hydroxide as a flame retardant; 40-55 parts of zinc borate and 7-10 parts of low melting point glass powder are used as flux.
2. The composite material according to claim 1, characterized in that The weight ratio between the PDMS component composed of vinyl-terminated polydimethylsiloxane and hydrogen-containing silicone oil and the filler component composed of hydroxyapatite nanofibers, aluminum hydroxide, zinc borate and low-melting-point glass powder is 100:85-115.
3. A method for preparing a composite material as claimed in claim 1 or 2, characterized in that: Firstly, hydroxyapatite nanofibers are synthesized by a hydrothermal method, and then hydroxyapatite nanofibers, zinc borate, aluminum hydroxide and low-melting-point glass powder are added to vinyl-terminated polydimethylsiloxane, mixed evenly by stirring, and then hydrogen-containing silicone oil is added and continued to be stirred evenly to obtain a pre-made slurry; the pre-made slurry is transferred into a mold, placed in a vacuum oven for vacuum degassing at room temperature, and finally hot-pressed, cooled and demolded to obtain a porcelainizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material that can be sintered and foamed at low temperature.
4. The method according to claim 3, characterized in that The preparation steps of synthesizing hydroxyapatite nanofibers by hydrothermal method are as follows: adding hexadecyltrimethylammonium chloride and oleic acid to an ethanol / deionized water solution and magnetically stirring at room temperature for a period of time, then slowly adding calcium chloride solution, sodium hydroxide solution and sodium dihydrogen phosphate solution in sequence and stirring for a period of time to prepare a precursor solution, and then transferring the precursor solution to a hydrothermal reactor for hydrothermal reaction; after the reaction is completed, washing the precipitate with ethanol and deionized water, and finally drying to obtain hydroxyapatite nanofibers.
5. The method according to claim 4, characterized in that The stirring time of the precursor solution preparation process in the method for synthesizing hydroxyapatite nanofibers is 20 to 30 minutes, and the molar ratio of Ca / P in the prepared precursor solution is 1.14:
1.
6. The method according to claim 4, characterized in that In the method for synthesizing hydroxyapatite nanofibers, the hydrothermal reaction temperature is 160-200° C., and the hydrothermal reaction time is 20-30 hours.
7. The method according to claim 4, characterized in that In the method for synthesizing hydroxyapatite nanofibers, the drying temperature is 60 to 80° C. and the drying time is 8 to 12 hours.
8. The method according to claim 3, characterized in that The stirring rate during the preparation of the pre-slurry is 200-400 rpm, and the total stirring time is 5-10 minutes.
9. The method according to claim 3, characterized in that The vacuum degassing time is 60 to 120 minutes, the hot pressing molding temperature is 100 to 150° C., and the hot pressing molding time is 5 to 10 minutes.
10. The ceramicizable flame-retardant PDMS / hydroxyapatite nanofiber silicone rubber composite material prepared by the method according to claim 1 or 2, or any one of claims 3 to 9, foams and expands during the sintering process to form a lightweight, porous, flame-retardant, and heat-insulating ceramic body.
Citation Information
Patent Citations
Flame-retardant microcrystalline cellulose / hydroxyapatite composite aerogel and preparation method thereof
CN108238595A